A New ID-based Threshold Ring Signcryption without Random Oracles - Hua Sun; Yanqiang Ge (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Signcryption is a cryptographic primitive which could provide authentication and confidentiality simultaneously with a computational cost lower than signing and encryption respectively, while the ring signcryption has anonymity in addition to authentication and confidentiality. In order to design an identity-based threshold ring signcryption, this paper presented an efficient identity-based threshold ring signcryption scheme without random oracles by means of secret sharing and bilinear pairing technique, and gave security analysis of the scheme. In the last, we proved this scheme satisfied indistinguishability against adaptive chosen ciphertext attacks and existential unforgeability against adaptive chosen message and identity attacks in terms of the hardness of DBDH problem and CDH problem.